Study on the Relationship between Audit Quality Perception and Corporate Governance - Mustatea, Aura Oana; Bulau, Carmen Mihaela; Badalau, Lucian Cosmin (Acta Universitatis Danubius. Œconomica, 2024)
The purpose of this study is to assess how the different elements of the audit process contribute to corporate governance. The sample comprises 124 firms, chosen using convenience sampling. The respondents are risk management specialists and internal auditors. To analyze the data, a structural equation model is employed. The results demonstrate a direct and positive correlation between the components of the audit process and the perception of corporate governance quality. These findings underscore the importance for organizations to adopt diverse practices that effectively allocate resources to enhance the quality of the audit process.